Mr. Lemoncello's library olympics - Grabenstein, Chris (New York : Random House, 2016)
"Mr. Lemoncello has invited teams from all across America to compete in the first ever LIBRARY OLYMPICS...but someone is trying to censor what the kids are reading"-- Provided by publisher.
Keywords: Libraries -- Fiction; Contests -- Fiction; Fiction